2011
DOI: 10.1111/j.2044-835x.2011.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between girls and boys in emerging language skills: Evidence from 10 language communities

Abstract: The present study explored gender differences in emerging language skills in 13,783 European children from 10 non-English language communities. It was based on a synthesis of published data assessed with adapted versions of the MacArthur-Bates Communicative Development Inventories (CDIs) from age 0.08 to 2.06. The results showed that girls are slightly ahead of boys in early communicative gestures, in productive vocabulary, and in combining words. The difference increased with age. Boys were not found to be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
272
8
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(337 citation statements)
references
References 34 publications
(47 reference statements)
43
272
8
14
Order By: Relevance
“…Linguistic skills are generally more advanced among girls than among boys (37,38). An investigation of over 13,000 children in 10 European linguistic communities suggests that these advantages are robust across different languages (38), although the level of overall linguistic attainment differed. Research on gender and mathematical competence suggests that there are widespread similarities between boys and girls (39).…”
Section: Discussionmentioning
confidence: 99%
“…Linguistic skills are generally more advanced among girls than among boys (37,38). An investigation of over 13,000 children in 10 European linguistic communities suggests that these advantages are robust across different languages (38), although the level of overall linguistic attainment differed. Research on gender and mathematical competence suggests that there are widespread similarities between boys and girls (39).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (12)(13) found in the literature also indicate a possible association between interpersonal communication and gender.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the large variation in language skills between communities, the difference between girls and boys remained. This suggests that the difference is caused by intrinsic factors that do not change between communities (12) . Another study concluded that the ability to perceive and understand others' intentions and actions depends on gender.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature in studying suboptimal development, or development of children with genetic disorders, we know that parents appear to be able to give an accurate estimation of what is happening not only in relation to their child’s general development when asked at the time of ‘happening events’, 46–49 but also in relation to more specific aspects, such as speech-language development. 50,51 The DNBC study offered us the opportunity to develop a new approach for investigating RTT through collecting quasi prospective and concurrent data on early development.…”
Section: Resultsmentioning
confidence: 99%